On zeros of the derivative of the Lerch zeta-function - Garunkštis, Ramūnas (Lietuvos matematikos rinkinys, 2002)
We consider zeros of the derivative of the Lerch zeta-function. We obtain some lower bound for the number of zeros lying on the right from the critical line.